2016
DOI: 10.1093/alcalc/agw092
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol and Alzheimer's Disease—Does Alcohol Dependence Contribute to Beta-Amyloid Deposition, Neuroinflammation and Neurodegeneration in Alzheimer's Disease?

Abstract: Alcohol use, misuse and dependence cause cognitive impairment. We propose alcohol adds to the cognitive burden seen in dementia through additional mechanisms to neurodegenerative processes or may contribute at various mechanistic points in the genesis and sustenance of AD pathology via neuroinflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 71 publications
4
45
0
Order By: Relevance
“…Here, we show that chronic, intermittent exposure to alcohol‐vapor that results in motivational and somatic signs of withdrawal, produces glial activation in hippocampus and thalamus identified by in vitro slice autoradiography with the TSPO ligands [ 3 H]PK11195 and [ 3 H]PBR28. Similar patterns of drinking in humans have been associated with signs of neurotoxicity and cognitive impairment (Gupta & Warner, ; Kopera et al., ; Venkataraman, Kalk, Sewell, Ritchie, & Lingford‐Hughes, ), and microglial activation and neuroinflammation are plausible contributing factors. Our findings contribute to a growing literature that support the hypothesis that alcohol exposure is associated with neuroinflammation in the brain (Crews et al., ; Marshall, Geil, et al., ; Obernier et al., ).…”
Section: Discussionmentioning
confidence: 75%
“…Here, we show that chronic, intermittent exposure to alcohol‐vapor that results in motivational and somatic signs of withdrawal, produces glial activation in hippocampus and thalamus identified by in vitro slice autoradiography with the TSPO ligands [ 3 H]PK11195 and [ 3 H]PBR28. Similar patterns of drinking in humans have been associated with signs of neurotoxicity and cognitive impairment (Gupta & Warner, ; Kopera et al., ; Venkataraman, Kalk, Sewell, Ritchie, & Lingford‐Hughes, ), and microglial activation and neuroinflammation are plausible contributing factors. Our findings contribute to a growing literature that support the hypothesis that alcohol exposure is associated with neuroinflammation in the brain (Crews et al., ; Marshall, Geil, et al., ; Obernier et al., ).…”
Section: Discussionmentioning
confidence: 75%
“…Alcohol has been examined as a risk factor of dementia, and a relationship between alcohol consumption and dementia has been evidenced. Although chronic alcohol abuse results in significant activation of neurodegenerative processes [23] and the prevalence of alcohol-related dementia represents about 10% of all cases of dementia [24], whether light-to-moderate drinking has any health benefits remains to be determined [25]. The relationship between the amount of alcohol intake and cognitive outcomes is complicated by differing definitions of high levels of alcohol consumption, by the duration of abuse, the age at which alcohol consumption begins, sex, and alternation of binge and withdrawal periods.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a prospective study of over 3000 subjects over 3 years found that light to moderate alcohol consumption reduced the risk of overall dementia by about 30% [ 83 ]. In contrast, a recent review of the literature to determine if alcohol consumption is a risk factor for AD concluded that alcohol use causes cognitive impairment by contributing to the neurodegenerative processes [ 84 ]. A systematic review concluded that there is as yet no consensus on this issue and that despite several studies, alcohol should not be considered methods to reduce AD risk [ 85 ].…”
Section: Discussionmentioning
confidence: 99%